2015
DOI: 10.1007/s00404-015-3973-x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapy of uterine clear cell carcinoma: a review

Abstract: For early stage disease, locoregional radiotherapy, especially vaginal brachytherapy, has evidence of efficacy. The therapeutic gain of radiotherapy may be further improved with the addition of systemic chemotherapy. Evidence for combined radiation therapy with systemic chemotherapy in women with advanced stage UCCC has remained debatable. UCCC-specific studies are needed to determine the best adjuvant therapy for UCCC without the confounding effects of USC and other endometrial cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…On the other hand, adjuvant RT has been applied for the treatment of early stage UCCC, a rationale inferred from the outcome data for women with uterine serous carcinoma and grade III endometrioid carcinoma (20). Lastly, Kim et al conducted a large retrospective analysis of 451 UCCC and 882 UPSC (uterine papillary serous carcinoma) patients from the SEER database and found that the 5-year OS for RT and non-RT patients at stage IB were 76% and 66% respectively (p = 0.006) whereas the 5-year OS for RT and non-RT patients at stage IC were 60.7% and 33.9% respectively (p = 0.001) (23).…”
Section: In the Latest Randomized Trial Of Radiation Therapy With Or mentioning
confidence: 99%
“…On the other hand, adjuvant RT has been applied for the treatment of early stage UCCC, a rationale inferred from the outcome data for women with uterine serous carcinoma and grade III endometrioid carcinoma (20). Lastly, Kim et al conducted a large retrospective analysis of 451 UCCC and 882 UPSC (uterine papillary serous carcinoma) patients from the SEER database and found that the 5-year OS for RT and non-RT patients at stage IB were 76% and 66% respectively (p = 0.006) whereas the 5-year OS for RT and non-RT patients at stage IC were 60.7% and 33.9% respectively (p = 0.001) (23).…”
Section: In the Latest Randomized Trial Of Radiation Therapy With Or mentioning
confidence: 99%
“…Foretinib treatment had significant effects in all of our in vivo experiments, and the most notable finding was that it led to the complete disappearance of the TEN cell tumor xenografts. This finding could be important for patients with uterine clear cell carcinoma because clear cell carcinoma is known to have a poor prognosis due to the high rate of drug resistance [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with endometrioid carcinoma (EC), patients with CCC have a worse prognosis ( 5 ). The 5-year overall survival rate of patients with higher International Federation of Gynecology and Obstetrics (FIGO) stage is below 50% ( 6 ).…”
Section: Introductionmentioning
confidence: 99%